(untitled) - Pierce, Pierce (Cambridge,New York, 1999)
The figure of the lost child has haunted the Australian imagination. Peter Pierce's original and sometimes shocking study The Country of Lost Children traces this ambivalent and disturbing history. Drawing on a wide range of sources, from poetry, fiction and newspaper reports to paintings and films, The Country of Lost Children analyses the cultural and moral implications of the lost child in our history and illuminates a crucial aspect of our present condition. At its core are confronting, often troubling, questions about childhood itself.
Keywords: Australian literature,Missing children in literature,Văn học Úc,Sự mất tích của những đứa trẻ; History and criticism,Lịch sử và phê bình